(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Mogiley I. V. Ways of spiritual needs formation of middle school students by means of the art complex at the music lessons. The problem of spiritual education in the theory and practice of comprehensive schools is concidered. The author emphasizes the relevance and importance of this direction of music pedagogy, examines the basic concepts, and suggests possible ways of spiritual needs formation of middle school students using the art complex.